درإسة تأأثير إلتطعيم على إلخوإص إلبنيوية للمركب La0.8(Ca1-X GdX)0.2MnO - منال, دركي; هاجر, هومة (My University, 2022)
يتركزززززالعززززز تلتير زززززلليرزززززتل ززززز رل ركززززز لتي ر ززززز ي لذ لتيصززززز لتي ئ ززززز لتير ززززز للللللللللللل La0.8(Ca1-xGdx)0.2MnO3لح زز لللXلن زز ل تيتطرزز ل(≥X≤0.20ل)0لبطريقزز ل رزز -لعزز. ل درتسزز ل زز رل عز تلتيتطرز يرزتلتياصز ئ لتي ن يز تي ز ئ ليز .لب نز لنتز ئ ل ط ز لتعةزر ل ز لتي زرتالرولكزللتيزر تب تير ي ل اتفيلبردل رحر لتيتر د ل زز ل ديززدلتي ن زز لتي ر ريزز لير ركزز ل تي در سزز لب سززتر لتي رنزز ل""Rex- Powder diffractionلتيزز ل يرت ززدليرززتل"ريقزز ل Rietveldليرت زز حيلح زز ل زز حلرولتي ركزز لليت رزز رل ززيلتيا ززرةلتيف زز ئ لPnmaيل رول حجزز لتيار زز ليت ززرلبت ززرلن زز لتيتطرزز لتي زز للتيتقززدير لي جزز لتي زز للبزز حلرولكززللتير نزز لن ن تريزز ل (15nmD20nm) ل ززز ل ديزززدلق ززز لتيف لزززللتيطززز ق ل)(Egلي زززللي نززز لب سزززتر ل "زززملتا تصززز فلي ةزززر ل ززز لللللل تي نف ج يل قدلك ن لق ت ل ترت حلب حل 2 6evل ل3eThis work was focused on the preparation using the sol-gel method and study of doping effect on the structural and optical properties of a perovskite compound with general chemical formula La0.8(Ca1-xGdx)0.2MnO3 (0≤X≤0.20). The infrared spectroscopy results showed that all the organic bonds disappear after the sintering stage. The crystallographic structure was determined using the "Rex- Powder diffraction" refinement program, based on the "Rietveld" method. It was found that the compound crystallizes in the Pnma space group, and that the cell volume changes with doping. The calculation of the estimated grain size showed that all samples were nanometric (15nmD20nm). Using the UV absorption spectrum, the energy gap (Eg) value for each sample, was determined and it was ranged between 2.6 eV and 3 eV
مذكرة ماستر فيزياء
Keywords: ريق ل ر -ع. يلتيتطر يلLa0.8(Ca1-xGdx)0.2MnO3يلتنررتجلتعةر لتي ن يلتعةر ل ل تي رتايلتعةر لتي رئ ل لتي نف ج ل; Sol-gel method, dopping, La0.8(Ca1-xGdx)0.2MnO3, X-Ray Diffraction, FTIR, UV-Visible.